Follow-Up of Head and Neck Cancer Survivors: Tipping the Balance of Intensity - Szturz, Petr; Van Laer, Carl; Simon, Christian; Van Gestel, Dirk; Bourhis, Jean; Vermorken, Jan B. (Frontiers in Oncology, 2020)
The traditional concept of post-treatment surveillance in head and neck cancer patients relies on examinations directed at early detection of disease recurrence and/or second primary tumors. They are usually provided by ear, nose and throat specialists with complementary input from radiation oncologists and medical oncologists. Emerging evidence underscores the importance of monitoring and effective management of late adverse events. One of the major drawbacks is a lack of prospective controlled data. As a result, local institutional policies differ, and practice recommendations are subject to continuing debate. Due to the economic burden and impact on emotional comfort of patients, intensity and content of follow-up visits are a particularly conflicting topic. According to the current evidence-based medicine, follow-up of head and neck cancer patients does not prolong survival but can improve quality of life. Therefore, an approach giving priority to a multidisciplinary care involving a speech and swallowing expert, dietician, dentist, and psychologist may indeed be more relevant. Moreover, on a case-by-case basis, some patients need more frequent consultations supplemented by imaging modalities. Human papillomavirus positive oropharyngeal cancer tends to develop late failures at distant sites, and asymptomatic oligometastatic disease, especially in the lungs, can be successfully salvaged by local ablation, either surgically or by radiation. The deep structures of the scull base related to the nasopharynx are inaccessible to routine clinical examination, advocating periodic imaging supplemented by nasofibroscopy as indicated. Anamnesis of heavy smoking justifies annual low-dose computed tomography screening of the thorax and intensive smoking cessation counseling. Finally, some cancer survivors feel more comfortable with regular imaging, and their voice should be taken into consideration. Future development of surveillance strategies will depend on several variables including identification of reliable predictive factors to select those who could derive the most benefit from follow-up visits, the availability of long-term follow-up data, the results of the first randomized trials, resource allocation patterns, infrastructure density, and the therapeutic landscape of locally advanced and recurrent and/or metastatic disease, which is rapidly changing with the advent of immune checkpoint inhibitors and better utilization of local approaches.